SPE Annual Technical Conference and Exhibition 2009
DOI: 10.2118/124631-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Automatic Control for Dual-Gradient Drilling

Abstract: Managed pressure drilling offers unprecedented capabilities for precise pressure control in drilling operations. This capability, created by the availability of new hardware tools, creates the need for tight coordination of such tools, to ensure reliable and safe operation. The use of model predictive control is proposed as a multivariable control framework that can coordinate multiple variables to offer both better performance and higher reliability and safety compared to current practice. A case study on a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We want to note that over the last 10 years, the oil and gas production industry has applied model predictive control (MPC)-based algorithm to drilling processes to enhance pressure control flexibility and process safety. [48][49][50][51][52][53][54][55][56][57][58][59] However, its application to hydraulic fracturing has not received much attention because of (a) limited availability of real-time measurements, (b) presence of uncertainties in the measurement data, and (c) large computational requirements due to the dynamic simulation of highly coupled PDEs defined over a time-dependent spatial domain.…”
Section: Introductionmentioning
confidence: 99%
“…We want to note that over the last 10 years, the oil and gas production industry has applied model predictive control (MPC)-based algorithm to drilling processes to enhance pressure control flexibility and process safety. [48][49][50][51][52][53][54][55][56][57][58][59] However, its application to hydraulic fracturing has not received much attention because of (a) limited availability of real-time measurements, (b) presence of uncertainties in the measurement data, and (c) large computational requirements due to the dynamic simulation of highly coupled PDEs defined over a time-dependent spatial domain.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear models increase the complexity of the calculations. Detailed description of supervisory control levels in drilling (MPD) operations are described in detail in Breyholtz et al (2009). The main objectives of an MPC controller are in prioritized order as follows (Qin and Badgewell 2003): 1.…”
Section: Supervisory Controlmentioning
confidence: 99%
“…If there are more MVs available than CVs, ideal resting values for the excessive MVs can be introduced. In Breyholtz et al (2009), such a system is demonstrated with an ideal resting value for the circulation rate. It is important to note that the ideal resting values will be obtained only as long as the first and second priorities are accomplished.…”
Section: Supervisory Controlmentioning
confidence: 99%
“…The nonlinear MPC model employed is described in detail in Breyholtz et al (2009c). The nonlinear solver in the MPC controller is a single-shooting multi-step quasiNewton method (Meum et al, 2008).…”
Section: System Descriptionmentioning
confidence: 99%